Trade relations of Kazakhstan with the countries of Central Asia: dynamics and development prospects (Journal of Economic Research & Business Administration, 2019)
The article discusses the current state and the main problems of foreign trade relations of Kazakhstan with the countries of Central Asia. The purpose of the study is to determine the significance for the Republic of Kazakhstan of trade with neighboring countries in the region, the barriers to mutual trade and its growth opportunities that exist today. The most important factor influencing the trade relations ofKazakhstan with the countries neighboring the region is the orientation of their foreign trade and, aboveall, of Kazakhstan itself to trade with countries outside the region. This situation has developed due tothe high availability of virtually all Central Asian countries with natural resources, primarily mineral resources.The methodology of the study is based on classical and modern theories of international trade,the theory of “new regionalism”, which allows to determine the causes, benefits, types of internationaltrade and barriers to its path. These theories make it possible to identify the economic and historicalbackground and growth opportunities of Kazakhstan’s trade with the countries of Central Asia. The mainresults of the study include the definition of the dynamics (over the last ten years) and the commoditystructure of trade of Kazakhstan with the countries neighboring the Central Asian region. The articlepresents indicators that make it possible to identify the significance of the republic’s foreign trade relationswith all countries of this region as a whole and separately with each of the countries: Uzbekistan,Kyrgyzstan, Tajikistan and Turkmenistan. The practical significance of the study lies in the analysis andassessment of the current state of Kazakhstan’s trade with the countries of its region, justifying the needand opportunities for its growth in the future. In order to ensure further development of Kazakhstan’strade relations with Central Asian countries, it is proposed to eliminate customs barriers, corruptionrelated to them, reduce transport costs by modernizing the transport system and, in general, developeconomic cooperation based not only on government agreements, but also on agreements between nongovernmentalorganizations and enterprises.